Konsep Tauhid Ismail Raji’ Al Faruqi dalam Islamisasi Ilmu - Tutik Haryanti; Amril M (Journal on Education, 2024)
The development of science for decades has been influenced by Western and Eastern philosophers, resulting in science that is considered too rationalistic and wastes humanity. This has a huge impact on Muslims, because the development of science causes a decline in morals and ethics that are not based on Islam. Therefore, the purpose of writing this article is to find out Ismail Raji' Al Faruqi's views on the Islamization of knowledge through the concept of monotheism. This research uses a qualitative descriptive approach with a literature review method. Where the author collects factual data and information and explores sources contained in journals and scientific articles, encyclopedias, documents and other relevant data sources. From the results of the analysis, it was found that the main thought of Ismail Raji' Al Faruqi was the concept of integrating Islamic education and science, namely combining two scientific fields to become interrelated and inseparable, so that science can develop harmoniously and there is no dichotomy. Islamization is not just the activity of naming Islamic verses or sciences, but rather the process of building an appropriate methodology based on Islamic concepts, ensuring that the sciences applied follow existing Islamic law.